DISCRIMINABILITY OF THE MINER SENTENCE COMPLETION SCALE AMONG SUPERVISORY AND NONSUPERVISORY SCIENTISTS AND ENGINEERS - Lacey, Lynn A. (Academy of Management Journal, 1974)
The article investigates whether the Miner Sentence Completion Scale, a measure of attitudes toward the supervisory job, differentiates between supervisory and nonsupervisory scientists and engineers employed by a government research and development laboratory. Differences significant at the .05 level were found for Imposing Wishes, Competitive Situations and Competitive Games and for the Item Score. Supervisors scored higher than nonsupervisors. The mean Item score for the combined supervisory and nonsupervisory groups in the sample is 2.78.